2016
DOI: 10.1161/circresaha.115.307765
|View full text |Cite
|
Sign up to set email alerts
|

Increased Epicardial Adipose Tissue Volume Correlates With Cardiac Sympathetic Denervation in Patients With Heart Failure

Abstract: Rationale: It has been reported that epicardial adipose tissue (EAT) may affect myocardial autonomic function.Objective: The aim of this study was to explore the relationship between EAT and cardiac sympathetic nerve activity in patients with heart failure. Methods and Results:In 110 patients with systolic heart failure, we evaluated the correlation between echocardiographic EAT thickness and cardiac adrenergic nerve activity assessed by Conclusions:This study provides the first evidence of a direct correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 50 publications
(67 reference statements)
2
56
0
2
Order By: Relevance
“…Recent data indicate a possible role of adipose tissue in modulating cardiac function [12, 42, 69]. It was reported that cardiac adipocytes are able to release substances that suppress the contraction of cardiomyocytes by attenuating intracellular Ca 2+ levels [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate a possible role of adipose tissue in modulating cardiac function [12, 42, 69]. It was reported that cardiac adipocytes are able to release substances that suppress the contraction of cardiomyocytes by attenuating intracellular Ca 2+ levels [49].…”
Section: Discussionmentioning
confidence: 99%
“…20 Of Interest, indirect evidence for the local toxic effect of cardiac ectopic fat on AF was recently shown by a surgical biopsy study. 21 That study demonstrated the increased concentration of norepinephrine, a catecholamine that invokes a sympathetic response, in epicardial adipose tissue, as compared to subcutaneous adipose tissue or plasma. 21 These findings support the biological plausibility of a relation between pericardial fat and AF as greater local catecholamine concentration may increase the occurrence of arrhythmia.…”
Section: Discussionmentioning
confidence: 93%
“…21 That study demonstrated the increased concentration of norepinephrine, a catecholamine that invokes a sympathetic response, in epicardial adipose tissue, as compared to subcutaneous adipose tissue or plasma. 21 These findings support the biological plausibility of a relation between pericardial fat and AF as greater local catecholamine concentration may increase the occurrence of arrhythmia. Nevertheless, we did not find associations between pericardial fat with incident AF after further adjusting for risk factor determinants of AF and BMI.…”
Section: Discussionmentioning
confidence: 93%
“…In this issue of Circulation Research, Parisi et al 18 report the results of their study looking at the relationship between epicardial adipose density and cardiac sympathetic denervation in patients with HF. The study involved 110 patients with HF of ischemic and nonischemic pathogenesis enrolled at the HF clinic of Federico II University of Naples, Italy.…”
mentioning
confidence: 99%